2009
DOI: 10.1021/nl9030709
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermally Reversible Assembly of DNA−Gold Nanoparticle Cluster Conjugates

Abstract: We describe the facile synthesis of stable gold nanoparticle clusters densely functionalized with DNA (DNA-AuNP clusters) using dithiothreitol and monothiol DNA and their thermally reversible assembly properties. The size of the clusters exhibits a very narrow distribution and can be easily controlled by adjusting the stoichiometry of dithiothreitol and DNA, leading to a variety of colors due to the surface plasmon resonance of the AuNP clusters. Importantly, the DNA-AuNP clusters exhibit highly cooperative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 56 publications
(113 reference statements)
1
69
0
1
Order By: Relevance
“…Metallic nanoparticles (NPs) have been shown to exhibit defined color changes between individual nanoparticles and aggregated clusters [37,38]. This characteristic has been used in colorimetric assays based on DNAfunctionalized gold nanoparticles (AuNPs) that provide an optical readout (visual color change) (Figure 2(c), top).…”
Section: Nanoparticle-basedmentioning
confidence: 99%
“…Metallic nanoparticles (NPs) have been shown to exhibit defined color changes between individual nanoparticles and aggregated clusters [37,38]. This characteristic has been used in colorimetric assays based on DNAfunctionalized gold nanoparticles (AuNPs) that provide an optical readout (visual color change) (Figure 2(c), top).…”
Section: Nanoparticle-basedmentioning
confidence: 99%
“…The solution was kept at room temperature for 30 min to destroy the formate esters formed in the reaction, after which it was poured into ice water (1.5 l). The precipitate was collected and Soxhlet extracted with methanol for 20 h. After rigorous drying, per-6-iodo-β-cyclodextrin was recovered as a white powder in 50% yield: MS m/z (positive ion ESI) 1903 for [M+Na] + , 1 H NMR (600 MHz, DMSO-d 6 δ) 3.24-3.68 (m, H-2, H-3, H-4, H-5, H-6a), 3.79 (bd, J = 9 Hz, 7 H, H-6b), 4.97 (d, J = 3 Hz, 7 H, H-1), 5.91 (7 H, OH-3), 6.02 (d, J = 5.4 Hz, 7 H, OH-2).…”
Section: Synthesis Of Per-6-iodo-β-cyclodextrinmentioning
confidence: 99%
“…Other DNA detection schemes have been reported, for example, one which is used as a capture oligonucleotide combined with a DNA probe attached to a gold nanoparticle. 47 This method can detect a single mismatch measured by resonance. Wu et al 48 reported the effect of different phosphate buffer concentrations suggesting that electrostatic repulsive forces between neighboring DNA molecules must play a role in cantilever motion and demonstrating that configurational entropy changes and the intermolecular interactions can control the direction of motion in nanomechanical sensors.…”
Section: State-of-the-artmentioning
confidence: 99%